A crítica de Nietzsche à formação do cristianismo em o anticristo - Silva, Hugo Leonardo Cavalcanti da (2015)
This paper seeks to analyze the most common interpretations of Nietzsche's concept of the Antichrist, listing the establishment of the distinction of the Christian theological morality and evangelical practice of Jesus. The philosophy of Nietzsche's hammer is present in this light, as deconstructed herd centuries of domination imposed by the Christian church. So discharge reading of Antichrist as a key work of clarifying the true intention of the dogmatic priests. The affirmation of life in this world and not in another is what makes the autonomous individual. The intellectual capacity and the critical sense shape the free man, the free-spirited man.